Tax instruments of environmental protection as seen in the example of tax reliefs associated with administration of real estate - Katarzyna Święch-Kujawska (Prawo Budżetowe Państwa i Samorządu)
This study undertakes crucial subject matter, from a practical and theoretical angle, of tax instruments of environmental protection associated with broadly understood administration of real estate. It is, besides, timely, especially due to the continuously progressing degradation of the natural environment and its impact on the social and economic environment. The basic research purpose was to establish whether the national legal order uses instruments that encourage this protection and, if yes, to what extent, at the same time assuming the validity of this system’s implementing non-fiscal purposes of taxation.